Early-Onset Neonatal Sepsis: A Retrospective Study among 1,119 Moroccan Newborns Admitted to the National Reference Center in Neonatology and Nutrition, Rabat, Morocco - Kenza Hattoufi; Majdouline Obtel; Hassan Aguenaou; Aicha Kharbach; Amina Barkat (Mashhad University of Medical Sciences, 2021)
Background: Early-onset neonatal sepsis is recognized as a common and serious problem for neonates. The clinical manifestations of neonatal sepsis are nonspecific and have varied clinical features. Therefore, their diagnosis is based on a combination of clinical presentation, the use of biological tests, and anamnestic arguments. The present study aimed to describe the infection risk factors, as well as clinical, paraclinical, and evolutionary characteristics of newborns with suspected early-onset neonatal sepsis and highlight the importance of C-reactive protein(CRP) to diagnose neonatal sepsis. Methods: This retrospective analytical study was conducted at the National Reference Center for Neonatology and Nutrition at Children's Hospital, University Hospital Centre IbnSina of Rabat, from January 1 to December 31, 2016. Results: During the study period, 1,199 newborns met the inclusion criteria. Upon admission, 52% of cases were under the age of one day. Symptomatic newborns represented 67.4% of the cases. The hospitalized cases with one or more infection risk factors were represented 80.3% of cases. The CRP was positive (> 20 mg/L) in 698 (58%) newborns. Univariate analysis pointed out that CRP value was significantly associated with age groups (P<0.001), presence of at least one infectious risk factor (P<0.001), as well as the presence of respiratory (P<0.001), cutaneous (P<0.001), circulatory (P=0.02), and neurological (P=0.008) symptoms. The diagnosis of early-onset neonatal infection with a meningeal, pulmonary, or ocular location was retained in 5%, 2%, and 0.2% of cases, respectively. The mortality rate was reported as 7%. Conclusion: Screening, management, and reduction of early-onset neonatal infection remain a crucial challenge, requiring coordination between pediatricians and obstetricians to obtain reliable data and identify newborns at risk.